Arousal-driven interactions between reward motivation and categorization of emotional facial expressions - Chakravarthula, Lakshman N. C.; Padmala, Srikanth (Frontiers in Psychology, 2022)
Reward motivation and emotion share common dimensions of valence and arousal, but the nature of interactions between the two constructs is relatively unclear. On the one hand, based on the common valence dimension, valence-compatible interactions are expected where reward motivation would facilitate the processing of compatible (i.e., positive) emotion and hamper the processing of incompatible (i.e., negative) emotion. On the other hand, one could hypothesize valence-general interactions driven by the arousal dimension, where the processing of both positive and negative emotions would be facilitated under reward motivation. Currently, the evidence for valence-compatible vs. valence-general type interactions between reward motivation and goal-relevant emotion is relatively mixed. Moreover, as most of the previous work focused primarily on appetitive motivation, the influence of aversive motivation on goal-relevant emotion is largely unexplored. To address these important gaps, in the present study, we investigated the interactions between motivation and categorization of facial emotional expressions by manipulating the valence dimension of motivation (appetitive and aversive motivation levels) together with that of emotion (positive and negative valence stimuli). Specifically, we conducted two behavioral experiments to separately probe the influence of appetitive and aversive motivation (manipulated via an advance cue signaling the prospect of monetary gains in Experiment 1 and losses in Experiment 2, respectively) on the categorization of happy, fearful, and neutral faces. We tested the two competing hypotheses regarding the interactions between appetitive/aversive motivation and emotional face categorization: Valence-compatible vs. Valence-general. We found evidence consistent with valence-general interactions where both appetitive and aversive motivation facilitated the categorization of happy and fearful faces relative to the neutral ones. Our findings demonstrate that interactions between reward motivation and categorization of emotional faces are driven by the arousal dimension, not by valence.